Corpus callosum abnormalities: neuroradiological and clinical correlations. (9th December 2015) - Al‐Hashim, Aqeela H; Blaser, Susan; Raybaud, Charles; MacGregor, Daune
Abstract : Aim: To study neuroradiological features in pediatric patients with corpus callosum abnormalities, using new functional subtyping for the corpus callosum, and to correlate the features with the clinical presentation. Method: We performed a retrospective review of 125 patients with radiologically identified abnormalities of the corpus callosum seen between 1999 and 2012. The study reviewed clinical features, genetic etiology, and chromosomal microarray (CMA) results. We used a new functional classification for callosal abnormalities based on embryological and anatomical correlations with four classes: complete agenesis, anterior agenesis (rostrum, genu, body), posterior agenesis (isthmus, splenium), and complete hypoplasia (thinning). We also studied the presence of extracallosal abnormalities. Results: The new functional callosal subtyping did not reveal significant differences between the various subtypes in association with neurological outcome; however, the presence of cardiac disease was found more frequently in the group with complete agenesis. Thirty‐seven per cent (46/125) had identifiable causes: of these, 48% (22/46) had a monogenic disorder, 30% (14/46) had a pathogenic chromosomal copy‐number variant detected by CMA or karyotype, and 22% (10/46) had a recognizable clinical syndrome for which no confirmatory genetic test was available (namely Aicardi syndrome/septo‐optic dysplasia and Goldenhar syndrome). The diagnostic yield for a significant CMA change was 19%. The presence of Probst bundles was found to be associated with a better neurodevelopmental outcome. Interpretation: The functional classification system alone 'without clinical data' cannot predict the functional outcome. The presence of extracallosal brain abnormalities and an underlying genetic diagnosis predicted a worse neurodevelopmental outcome. This study highlights the importance of CMA testing and cardiac evaluation as part of a routine screen. What this paper adds: The yield of chromosomal microarray testing is high, even in cases of isolated callosal agenesis. It highlights the significant association of cardiac anomalies in isolated and complete agenesis of the corpus callosum. The functional anatomical classification system in isolation was not able to predict neurological outcome. The presence of extracallosal and extra‐central nervous system malformation together with the detection of a neurogenetic etiology are the main predictors of clinical outcome. This article is commented on by Palmer on pages430–431 of this issue.